Investigating the Relationship between Brand Attributes and Brand Loyalty Among Tooth Paste Users in Greater Accra Region of Ghana - Martey , Edward Markwei; Frempong, Joseph (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
The purpose of this study is to investigate the association between brand attributes and brand loyalty among tooth paste users in Greater Accra region of Ghana. The main objective is to examine the relationship between brand attributes on brand loyalty. Four hundred and twenty one (421) copies of questionnaires were retrieved through convenient sampling method. With the aid of Statistical Package for Social Sciences (SPSS) the following statistics were employed: Descriptive statistics, Cranach’s alpha, Kurtosis and Skewness and Regression analysis were used to measure the relationship of independent variables (packaging, price, and brand awareness) on dependent variable (brand loyalty).The findings revealed that all three attributes of brand; packaging, price and brand awareness had a significant and positive relationship with brand loyalty. The research suggests that tooth-paste producers in Ghana should adopt green packaging marketing strategy to outwit multinational competitors.